Ekonomi Kreatif Sebagai Strategi Peningkatan Perekonomian Masyarakat Lokal di Sekitar Farmhouse - Nissa, Mutya Aulia; Noviandhita, Reffasya; Tobiha, Shifa Aura; Alifah, Tanaya Salma (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Farmhouse Lembang is a tourist destination in Gudang Kahuripan Village, Lembang District, which was founded in 2015. This destination offers various interesting attractions for visitors because it carries a European-style concept. The increasing number of tourists has led to the use of the potential of the creative economy to attract tourists and generate profits, both through product sales and service provision. This research aims to determine the creative economic activities implemented by local communities around the Farmhouse. This research is based on a qualitative descriptive approach and uses primary data. In this research, six Lembang residents who worked at the Farmhouse were involved as resource persons. Interviews and observations were used to collect data. Research data shows that the community promotes and creates anti-mainstream businesses, as well as collaborating with Farmhouse to improve business. The existence of creative economic activities can provide a positive side to local communities such as helping the economy, reducing poverty and changing livelihoods.